Pollen and seed yield components of water-stressed cultivated and weedy rice - Puteh, Adam; Jali, Normaliana; Ismail, Mohd Razi; Juraimi, Abdul Shukor; Samsudin, Nuzuliati (Universiti Putra Malaysia Press, 2009)
Water stress occurring during the early phase of the reproductive growth stage may influence plant reproduction success. The objectives of this study were to evaluate the responses of pollen and seed yield components to water stress during anthesis in cultivated rice (Oryza sativa L.) varieties and weedy rice strains. Studies were conducted in 2007 using three cultivated rice varieties; MR 84, MR 219 and MR 232. In 2008 three weedy rice strains were obtained from Seberang Perak, Kuala Pilah and Tanjung Karang areas. Studies were conducted in the field where plants were grown in polybags and submerged in polyethylene tanks. Prior to anthesis, plants were subjected to water stress by taking the plants out of the polyethylene tanks for five days. Flag leaf relative water content (RWC) and relative injury (RI) were measured daily during the stressed period. Pollen production and pollen viability were measured upon re-watering. Seed yield components measured were grain number per panicle, 100-grain weight, percentage filled grain and percentage spikelet sterility at harvest. Water stress caused a 13 – 34% decline in the number of pollen grains per anther in cultivated varieties but increased pollen production in weedy strains. Percentage pollen viability declined by 40 – 45% in MR 219 and MR 232, but increased by 15% in MR 84 when plants were water-stressed. Percent pollen viability in weedy strains never exceeded 52% and significantly declined with water stress. For cultivated varieties, water stress increased total number of grain per panicle by 31%. In weedy strains, only Seberang Perak increased in the number of grain per panicle due to water stress. Spikelet sterility was relatively higher in cultivated varieties (16 – 50%) compared with weedy strains (10 – 23%). The 100-grain weight was not affected by water stress in both cultivated varieties and weedy strains. This study indicated that weedy rice strains would gain a competitive advantage by producing more filled grains when water deficit occurs during anthesis.